al-Asālību al-Chujājiyyatu li Shāchibi al-Chujjah ‘alā Ahli al-Madīnah - Mohammed Ahmed Aloraini (Universitas Negeri Malang, 2023)
This research aims to look at the argumentative methods of Mohammad ibn Al-Hasan Al-Shaibani, author of the book “The argument against the People of Medina,” which he wrote in response to some jurisprudential opinions of the people of Medina. The title chosen for his book has a clear argumentative indication(the argument against the people of Medina); He proceeded from it to argue with the people of Medina in various opinions, and the research discussed the synthesis methodology on which Mohammad ibn Al-Hasan Al-Shaibani built his argumentative style, which revealed his mentality that enabled him to emerge, and then the various methods that he employed and were between sarcasm; To degrade the abnormal opinions in his opinion, and his reliance on inference in his arguments, diversifying his use of the interrogative, and luring the opposed to set him in what he wants, highlighting his contradiction, and employing the preventive method, and the method of measurementيروم هذا البحث النظر في الأساليب الحجاجية لمحمد بن الحسن الشيباني مؤلف كتاب الحجة على أهل المدينة الذي ألفه ردًا على بعض الآراء الفقهية لأهل المدينة، ووظف بذلك عددًا من الأساليب الحجاجية التي مكنته من إيراد آرائه للمتلقين وحجاج خصومه، ويبرز الحجاج من عتبته قبل الولوج فيه حينما اختار لكتابه هذا العنوان (الحجة على أهل المدينة)؛ فانطلق منه نحو حجاج أهل المدينة في آراء شتى، وناقش البحث المنهجية التأليفية التي بنى عليها محمد بن الحسن الشيباني أسلوبه الحجاجي التي كشفت عن عقليته التي مكنته من البروز، ثم الأساليب المتنوعة التي وظفها وكانت ما بين التهكم؛ للحط من قدر الآراء الشاذة برأيه، واعتماده على الاستدلال في حجاجه، وتنويع استخدامه للاستفهام، واستدراج مخالفه لإيقاعه فيما يريد، وإبراز تناقضه، وتوظيفه للأسلوب الوقائي، وأسلوب القياس.